Análisis del Comportamiento del Canal E-Commerce y el Marketing Digital en Almacenes Corona S.A.S Antes y Durante la Pandemia por el Covid - 19 (2021)
With the arrival of the Covid-19 pandemic, the business sector suffered many effects that forced it to reinvent itself in an operational and structural way, to be able to respond to the new needs of the market and also adapt to the changes generated by preventive isolation. In this sense, BBVA (2020) states in its report that “digital media in times of confinement have facilitated purchases through 'e-commerce' stores and 'online' orders. Many companies and SMEs have had to adapt quickly to this new reality, and accelerate their digital transformation ”(p.1). In this way, electronic commerce and digital marketing have allowed products and services to be visible in the midst of preventive isolation and regardless of geographical location, that is, these tools have allowed the relationship between the company and the customer to not deteriorate. consumer, mitigating negative effects, increasing visibility of products and services and increasing sales